PECULIARITIES OF INHERITANCE AND TRANSGRESSIVE VARIABILITY OF GRAIN NUMBER IN INTRASPECIFIC HYBRIDISATION OF WINTER BREAD WHEAT - Halyna USTYNOVA; Mykola LOZINSKYI; Mykola GRABOVSKYI; Igor POKOTYLO; Yurii FEDORUK; Valerii KHAKHULA; Oksana LUPITKO; Taras PANCHENKO; Anatolii ALDOSH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In 2018-2020, the peculiarities of inheritance of grain number of the main spike in F1 and transgressive variability in F22 populations were studied in intraspecific hybridisation of early, medium early and medium late winter wheat (Triticum aestivum L.) varieties. It was found that in 97.5% of the hybrids the inheritance of grain number was based on positive superdominance with modification of phenotypic dominance (hp) depending on the selected hybridisation pairs and the year conditions. The excess of the extreme maximum grain number of the main spike over the parental forms in 18 (2019) and 14 (2020) F2 populations of 20 crossing combinations with a positive degree of transgression (Тd = 4.3-60.0%) and the frequency of breeding valuable recombinants (Тf = 3.3-66.7%) were studied. Positive correlations (r = 0.932; r = 0.977) between the positive degree and the frequency of transgressive recombinants were found to be very strong and close to functional correlations (r = 0.932; r = 0.977). The inclusion of varieties of different vegetation periods in hybridisation contributes to the formation of F2 populations with the possibility of selecting economically valuable recombinants by the number of grains per main ear.